The Study to Analyze the Impact of Green Supply Chain Management in India - Shalini Srivastava; Vikas Garg; Pooja Tiwari (International Journal of Supply Chain Management, 2019)
Green supply chain management can be explained as a supply chain management system which is beneficial for the environment and which consists of designing of products , selection of raw material,manufacturing steps and delivery and preparation of final product through a stable and sustainable process.Sustainibility is the major key to supply chain ,which starts with the understanding through all the phases of production upto final distribution. This paper majorly focuses on the importance and need of term green and concepts or activities which are related to greener activities in areas like manufacturing and remanufacturing of products having a green impact ,controlling of travel costs and waste products , reverse logistics etc. The purpose is to understand the impact and also to make people aware about the major difficulties, problems and also the advantages and profits which are a part of such a great green concept if it is successfully implemented or installed during the process of supply chain management in various organisations.Keywords : Production, customer , supply chain , green , sustainability , manufacturing , materials.